Child health in Latin America: historiographic perspectives and challenges Saúde infantil na América Latina: perspectivas historiográficas e desafios - Anne-Emanuelle Birn (História, Ciências, Saúde: Manguinhos)
Patterns of child health and well-being in Latin America's past - have been assumed to be delayed and derivative of European and North Americanexperiences. Through an examination of recent historiography, this essay traces a more complex reality: interest in infant and child health in Latin America arose from a range of domestic and regional prerogatives. This attention was rooted in preColumbian cultures, then relegated to the private sphere during the colonial period, except for young public wards. Starting in the 19th century, professionals, reformers, and policy-makers throughout the region regarded child health as a matter central to building modern societies. Burgeoning initiatives were also linked to international priorities and developments, not through one-way diffusion but via ongoing interaction of ideas and experts. Despite pioneering approaches to children's rights and health in Latin America, commitment to child well-being has remained uneven, constrained in many settings by problematic political and economic conditions uch. Modelos de saúde e bem-estar infantis do passado na América Latina têm sido considerados como subprodutos defasados de experiências européias e norte-americanas. Com base em análise da historiografia recente, este artigo apresenta uma realidade mais complexa: o interesse pela criança e a saúde infantil na América Latina origina-se de um conjunto de condições domésticas e regionais. Com raízes em culturas pré-colombianas, foi relegado à esfera privada no período colonial, exceto quanto à custódia pública de jovens. A partir do século XIX, profissionais, reformadores e políticos de toda a região passaram a considerar a saúde infantil fundamental para a construção das sociedades modernas. As iniciativas que emergiram desde então guardam relação também com prioridades e programas internacionais, não por difusão unidirecional mas sim pela interação de idéias e especialistas. Apesar das abordagens pioneiras sobre direitos e saúde da criança na América Latina, o compromisso com o bem-estar infantil permanece irregular, e em muitos contextos cerceado por condições políticas.